Solitary Confinement Of Inmates As A Form Of Extreme Marginalization - Ignjatović, Đorđe M. (Sociološki pregled, 2020)
Confinement of persons, perpetrators of acts that the community deems unacceptable prior to being sanctioned or punished is a phenomenon that goes back to the earliest period of human civilization. It was not until the transition from the Middle Ages to the new century that it became a legally regulated way of responding to crime. With the introduction of the punishment of confinement in the register of criminal sanctions, the first institutions which carried out confinement were created. Interestingly, the first conceived modality of confinement entailed strict solitary confinement and was soon abandoned due to the serious shortcomings it showed. However, in the last decades of the twentieth century, with the establishment of supermax units, this model has re-emerged, first in the United States and then in many other countries. Although numerous studies have shown how harmful this type of punishment to persons who are isolated for a long time is, the model survives and even shows a tendency to spread. Serbia’s legal system has also not been spared of the new mode of marginalization of confined persons, which applies to the perpetrators of most serious crimes, and above all those belonging to the category of organized crime. Recent changes to the criminal code create the possibility of coming even closer to the model existing in the US, as well as expanding the circle of persons to whom it shall apply.